Entrepreneurial Orientation and Accounting Information Quality in Enhancing Business Sustainability in India - Ram Singh (PT. BATARI EDU CALYA, 2025)
This study investigates the relationship between entrepreneurial orientation (EO) and accounting information quality in enhancing business sustainability among enterprises in India. The research employs a quantitative methodology, using survey instruments administered to 150 small and medium-sized enterprises (SMEs) across multiple industrial sectors in India. Data analysis was conducted using Structural Equation Modeling with Partial Least Squares (SEM-PLS) to examine the hypothesized relationships between entrepreneurial orientation dimensions (innovativeness, proactiveness, risk-taking), accounting information quality indicators (relevance, reliability, and timeliness), and business sustainability outcomes. The findings reveal that entrepreneurial orientation significantly influences business sustainability, with accounting information quality serving as a mediating variable in this relationship. Specifically, enterprises demonstrating higher levels of entrepreneurial orientation exhibit superior accounting practices, which subsequently contribute to enhanced sustainable performance. The results indicate that e-commerce adoption and entrepreneurial orientation have substantial impacts on the sustainability of small business performance (Purty, 2025). Furthermore, the study confirms that entrepreneurial orientation influences social capital and market capabilities, which in turn affect marketing performance (Farida et al., 2017). These findings provide valuable insights for policymakers and business practitioners in developing strategies to support sustainable enterprise development in India, particularly in addressing the challenges faced by small and medium enterprises in achieving long-term viability while maintaining competitive advantage in dynamic market environments.